Repeated proceedings against suspected illicit wealth – justifiable protection of public interest or violation of human rights? - Bikelis, Skirmantas (Kriminologijos studijos, 2021)
The internationally acknowledged need for effective legal measures against illicit enrichment that is perceived as the key policy tool against organised crime and corruption triggered rapid developments in the variety of those legal measures. Lithuania may serve as a sole-standing example of a jurisdiction that enacted a great variety of legal strategies against illicit enrichment – criminal liability both for money laundering and illicit enrichment and also extended powers of confiscation, civil confiscation and tax fines for unexplained income. This diversity of measures leads to the issue of competition arising between them and also carries the risk that measures may be used repeatedly and arbitrarily against persons and their property.The paper focuses on the issue of the legitimacy of repeated investigation and assessment of suspicious assets in civil confiscation proceedings and extended powers of confiscation.The analysis is divided into two parts where fundamentally different legal situations are discussed. In the first situation, repeated assessment of the origin of the assets takes place in proceedings of similar legal nature (proceedings aiming to restore legal order). The second situation appears where reassessment takes place in proceedings of a different nature – in the restorative proceedings after failure to prove the illicit origin of the assets in the punitive proceedings.While the first situation rather clearly falls within the scope of the principle of legal certainty and the rule res judicata that prohibit repeated proceedings for the same issue in the same circumstances against the same person, the second situation is more open to debate. Punitive proceedings use the standard of proof beyond reasonable doubt and the presumption of innocence is in play. These safeguards are designed to protect defendants from unfounded conviction, but they may be considered excessive for other legal issues such as the recovery of damages or the proceeds of illicit activities. In addition, in the context of civil confiscation, public interest in effective protection from organised crime and corruption comes into play. Therefore, there are strong arguments for giving priority to public safety over the principle of legal certainty that would protect defendants from repeated assessment of their assets in other proceedings with a lower standard of proof or even the reversed presumption of the illegality of unexplained wealth.Finally, the paper addresses the question of whether extended powers of confiscation qualify for restorative or punitive proceedings. The answer to this question is the key argument of whether civil confiscation proceedings can legitimately follow criminal proceedings where the court failed to confiscate the assets on the grounds of extended powers of confiscation. The paper argues that extended powers of confiscation are of a restorative nature. Therefore, when assets have already been investigated in proceedings of civil confiscation and their origin has been assessed as lawful in the light of extended powers of confiscation, re-consideration of their origin should be deemed as infringing the principle of legal certainty, unless the decision in the criminal proceedings was barred by lack of formal grounds.
Keywords: civil confiscation; illicit enrichment; non bis in idem; repeated proceedings